Role of Human Resource in Quality Enhancement of Tourism Service in Pokhara - Bhandari, Arjun Bahadur (Janapriya Journal of Interdisciplinary Studies, 2022)
The Nepal Tourism Policy 2009 recognizes tourism as a key driver for the country and economic growth by creating job opportunities and producing foreign reserves. Tourism policy has been developed to promote the growth and extension of tourism activities, the quality improvement of tourism services, the increase of income, and the expansion of job possibilities in order to enhance Nepalese people living standards. Quality reflects several elements of tourism, such as physical, natural, and environmental. It also focuses on quality tourism; however, officials and tourist operators are divided on the subject. Tourism in Pokhara is increasingly transitioning to mass tourism. As a result, it appears that the moment has come to incorporate quality tourism concepts in the sector. The ecological, economic, and socio-cultural components of tourist development, as well as an appropriate balance between these three dimensions, are referred to as sustainability principles. It also aims to increase the quality of infrastructure and human resources. Role of human resources are always vital ensuring quality assurance. Hence it is the time to address the importance of human resource enhancing quality in the industry. This is a historical study based on qualitative research method. In this study, descriptive and analytical methods were used to investigate the importance of examining and analyzing the challenges faced by the tourism industry in terms of quality, human resources in order to ensure the long-term sustainability of the Nepalese tourism industry. This article focuses mostly on the quality of tourism through human resources. Tourist satisfaction is determined by their actions and attitudes, which is a source of worry in the Nepalese tourism business, particularly in Pokhara.